A study of pipe leak source location using single channel acoustic emissions (AE) technique - Mohd Firzikri, Abd Sata (2009)
This project was carried out as a study of pipe leak source location using single channel acoustic emissions (AE) technique. The objectives of this project are to study a reliable and affordable system capable of monitoring pipe leak and also to locate the source of the pipe leak using AE technique. A test rig consists of the pipe without leak and the pipe with leak was developed using circumferential of a galvanized steel pipe to run the experiments. The fluid used was water throughout the experiments. The flow of the water was controlled by a ball valve. The source of the AE signals was from the leak and it was captured using AE sensor with the help of Acoustic Emission Detector 2.1.3 software. For all pipe conditions, the values of hits, counts and RMS (average, maximum and minimum) were recorded and analyzed. All the values recorded were compared between the pipe without leak and the pipe with leak (full open valve and full close valve). The results were gained from 8 marked points each for all pipe conditions. The results showed that there was no AE activities on the pipe without leak while for the pipe with leak, the AE activities are greater for full close valve than full open valve. In addition, two equations for locating the source of the pipe leak were introduced from the RMS against distance graft. For the pipe with leak and full open valve, the equation is y = 0.011 x + 0.249. For the pipe with leak and full close valve, the equation is y = 0.017 x + 0.199.